Photoinduced Intervalence Charge Transfers: Spectroscopic Tools to Study Fundamental Phenomena and Applications. Issue 20 (19th October 2022) - Ramírez‐Wierzbicki, Ivana; Cotic, Agustina; Cadranel, Alejandro
Abstract: The front cover artwork is provided by Dr. Alejandro Cadranel's group at the University of Buenos Aires and the Friedrich‐Alexander Universität Erlangen‐Nürnberg. The image shows a ground state that forms, upon photon absorption, an excited state mixed valence system, which is characterized by a double‐well potential energy surface. Inspection of the excited state with light reveals photoinduced intervalence charge transfers (cover design by Gonzalo Peñaloza). Read the full text of the Concept at 10.1002/cphc.202200384 . Abstract : "We review photoinduced mixed valence systems, which are excited states prepared from non‐mixed valence ground states upon light absorption. The resulting transient species present photoinduced intervalence charge transfers (PIIVCT) in the NIR, which can be analyzed employing the same formalisms developed for their ground state analogs. PIIVCT are a valuable spectroscopic tool that reveals not only details about donor‐acceptor interactions in the excited state, but also mechanistic details regarding excited state decay…" This and more about the story behind the front cover can be found in the Concept at 10.1002/cphc.202200384 .